Paroxysmal Sympathetic Hyperactivity in Severe Anti-N-Methyl-d-Aspartate Receptor Encephalitis: A Single Center Retrospective Observational Study - Wang, Dongmei; Su, Shuang; Tan, Miaoqin; Wu, Yongming; Wang, Shengnan (Frontiers in Immunology, 2021)
Background: Paroxysmal sympathetic hyperactivity (PSH) is a disorder with excessive sympathetic activity commonly recognized in patients with acquired brain injury. Autonomic instability is frequent in anti-N-methyl-d-aspartate receptor encephalitis (anti-NMDARE). However, PSH in anti-NMDARE has gained little attention. Methods: We retrospectively reviewed 24 patients diagnosed with severe anti-NMDARE in the neuro-intensive care unit (NICU) between 2014 and 2019. Patients were assessed with the PSH assessment measure (PSH-AM) scale, and categorized into “PSH+” group and “PSH-” group. The clinical characteristics, hospital mortality, and functional outcome by modified Rankin Scale (mRS) score at six months after discharge were compared between the two groups. Among patients with PSH+, the clinical features and pharmacotherapy of PSH were summarized and compared. Results: Twenty-four patients were included in the study. Twelve of them (50%) were categorized as PSH+ based on PSH-AM scores. There were no significant differences in the demographic characteristic, GCS scores upon admission, incidence of status epilepticus, teratoma occurrence, hospital mortality, and 6-month mRS between PSH+ and PSH- groups. Patients with PSH+ had increased length of NICU stay, hospital stay and duration of mechanical ventilation. The most prominent clinical features of PSH in severe anti-NMDARE were tachycardia and hyperthermia, while posturing was the relatively mildest clinical feature. Propranolol and clonazepam were more commonly used than gabapentin in pharmacotherapy of PSH in severe anti-NMDARE. Conclusions: The incidence of PSH in severe anti-NMDARE patients was as high as 50%. Patients with PSH demonstrated prolonged NICU stay, hospital stay and increased duration of mechanical ventilation, while no effect on hospital mortality and functional outcome. Clinicians should be aware of the distinctive characteristics and treatment options of PSH in severe anti-NMDARE.